2017
DOI: 10.1016/j.omtn.2016.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Systemic RALA/iNOS Nanoparticles: A Potent Gene Therapy for Metastatic Breast Cancer Coupled as a Biomarker of Treatment

Abstract: This study aimed to determine the therapeutic benefit of a nanoparticular formulation for the delivery of inducible nitric oxide synthase (iNOS) gene therapy in a model of breast cancer metastasis. Nanoparticles comprising a cationic peptide vector, RALA, and plasmid DNA were formulated and characterized using a range of physiochemical analyses. Nanoparticles complexed using iNOS plasmids and RALA approximated 60 nm in diameter with a charge of 25 mV. A vector neutralization assay, performed to determine the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 48 publications
0
14
1
Order By: Relevance
“…In the downstream signaling pathway, Ral small GTPases (RalA), a member of the Ras branch of the Ras superfamily (19), has been shown to be significantly activated in colorectal cancer tissues and cell lines positively regulating cell growth and proliferation in a study by Martin et al (20). RalA is also involved in multifarious cancer progression, such as cervical cancer (21), hepatocellular carcinoma (22), chronic myelogenous leukemia (23), lung cancer (24), colorectal cancer (20), breast cancer (25) etc. In addition, Ral proteins mediate their activities through multiple downstream effectors, of which Ral binding protein-1 (RalBP1) is an important downstream effector, which is expressed at higher levels in cancer cells (26,27).…”
mentioning
confidence: 99%
“…In the downstream signaling pathway, Ral small GTPases (RalA), a member of the Ras branch of the Ras superfamily (19), has been shown to be significantly activated in colorectal cancer tissues and cell lines positively regulating cell growth and proliferation in a study by Martin et al (20). RalA is also involved in multifarious cancer progression, such as cervical cancer (21), hepatocellular carcinoma (22), chronic myelogenous leukemia (23), lung cancer (24), colorectal cancer (20), breast cancer (25) etc. In addition, Ral proteins mediate their activities through multiple downstream effectors, of which Ral binding protein-1 (RalBP1) is an important downstream effector, which is expressed at higher levels in cancer cells (26,27).…”
mentioning
confidence: 99%
“…The improvement in survival in this prostate cancer model was much higher (56% increase in median survival in the PC-3 model versus a 27% increase in median survival in the breast cancer model), although an explanation for this has not been ascertained. MDA-MB-231 breast cancer cells are a notoriously aggressive model of breast cancer, and the progression of disease was faster in that model (the median survival of control mice in this study was 90.5 days, but only 31.5 days in the breast model), which may account for the observed differences (McCrudden et al 2017 ).…”
Section: Discussionmentioning
confidence: 61%
“…It was previously reported that RALA/iNOS nanoparticulate gene therapy produced ·NO production in vitro, and improved survival following systemic administration in a model of breast cancer metastasis (McCrudden et al 2017 ). The results reported here reinforce those findings in prostate cancer.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…2) [97]. RALA has been utilised to deliver a range of cargo including plasmids encoding reporter genes, small interfering RNA (siRNA), messenger RNA (mRNA), and therapeutic plasmids, in addition to anionic small molecule (such as bisphosphonates) and incorporation into polymeric microneedles [97,[101][102][103][104][105]. This demonstrates the immense potential of RALA as a CNS delivery agent, highlighting the versatility of fusogenic peptides in general.…”
Section: Peptide-based Vectorsmentioning
confidence: 99%